Karawitan Art as Local Cultural Wisdom in the Management of Autism Spectrum Disorder - Sukinah, Sukinah (HM Publisher, 2020)
To arrange all life to be in harmony in worldly and spiritual / inner life is the view of life and daily life of the Javanese people in general, for example how to dress properly, harmony in speaking even though they are in an explosive inner emotion, still trying to be polite in expressing their hearts. Children with special needs are part of the nation's children who have the same rights in all aspects of life in this country, including one of which is preserving local culture that has existed for a long time. One of the children with special needs is an autistic child who has complex developmental disorders including barriers in social interaction, deficient or excessive behavior and language barriers, so they need various alternative management. This literature review aims to discuss the use of musical arts as an effort to rehabilitate children with autism spectrum disorder.